COVID-19 Crisis and the State of Emergency: Analyzing Impacts, Paradoxes, and Recommendations - Neamah, Salim; Rawdhan, Ahmed; Rashed, Haeder (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article examines the exceptional situation that emerged during the COVID-19 pandemic and the subsequent imposition of states of emergency, which raised concerns about potential abuses of power by governments. Employing analytical and comparative approaches, the research explores the connection between the pandemic and its effects on human rights and freedoms, particularly regarding movement and assembly restrictions. The study highlights the diverse implementation of states of emergency across countries during the crisis. The findings reveal international gaps in preparedness, the violation of human rights, and the potential exploitation of emergencies for other purposes. Recommendations include enhancing international cooperation, reevaluating intellectual property rights related to combating epidemics, establishing a global health cooperation fund, setting reasonable limits for emergency measures, and implementing internal monitoring committees to ensure the proportionality of restrictions. These insights have significant implications for global health security, human rights protection, and international collaboration in response to future health emergencies.Highlights: Impact of state of emergency: Examining the repercussions of COVID-19 pandemic emergency measures on human rights. Global health challenges: Assessing health system effectiveness in confronting COVID-19 and its impact on human rights. Recommendations for action: Proposing measures for international cooperation, intellectual property rights reconsideration, establishing a health cooperation fund, setting reasonable emergency limits, and implementing monitoring committees. Keywords: COVID-19, state of emergency, human rights, global health, recommendations.